High Neutrophil-to-Lymphocyte Ratio Predicts Hemorrhagic Transformation in Acute Ischemic Stroke Patients Treated with Intravenous Thrombolysis. (28th February 2020) - Liu, Yong-Lin; Lu, Jie-Kai; Yin, Han-Peng; Xia, Pei-Shan; Qiu, Dong-Hai; Liang, Man-Qiu; Qu, Jian-Feng; Chen, Yang-Kun
Abstract : Background . The relationship between the neutrophil-to-lymphocyte ratio (NLR) and hemorrhagic transformation (HT) in acute ischemic stroke (AIS) treated with intravenous thrombolysis (IVT) remains unclear. This study assessed whether high NLR is associated with HT in this population. Methods . Data were prospectively collected for continuous patients with AIS treated with IVT and retrospectively analyzed. Clinical variables included age, sex, vascular risk factors, National Institutes of Health Stroke Scale (NIHSS) score, onset-to-treatment time, and initial hematologic and neuroimaging findings. HT was confirmed by imaging performed within 3 days after IVT. Symptomatic HT (sHT) was defined as NIHSS score increased by 4 points compared with that on admission according to previously published criteria. The NLR value was based on the blood examination before IVT, and high NLR was defined as ≥75th percentile. Results . The study included 285 patients (201 (70.5%) males, the mean age was 62.3 years (range 29–89)). Seventy-two (25.3%) patients presented with HT, including three (1.1%) with sHT. The median NLR was 2.700 (1.820–4.255, interquartile range). Seventy-one (24.9%) patients had a high NLR (≥4.255) on admission. Univariate analysis indicated that patients with HT had higher NIHSS scores (P < 0.001 ), systolic blood pressure (SBP), platelet counts, lymphocyte counts, and NLR (P < 0.05 ), as well as a greater prevalence of high NLR than those without HT (37.5% vs. 20.7% and P = 0.004 ). Patients with HT were more likely to have hypertension and AF. As lymphocyte counts and high NLR were highly correlated, we used two logistic regression models. In model 1 (with high NLR), NIHSS score on admission (odds ratio (OR) = 1.110, 95% confidence interval (CI) = 1.015–1.044, and P = 0.001 ), AF (OR = 3.986, 95% CI = 2.095–7.585, and P < 0.001 ), and high NLR (OR = 2.078, 95% CI = 1.078–4.003, P = 0.029, sensitivity 0.375, and specificity 0.793) were significant predictors of HT. In model 2 (with lymphocyte counts), NIHSS score on admission (OR = 1.111, 95% CI = 1.050–1.175, and P < 0.001 ), AF (OR = 3.853, 95% CI = 2.048–7.248, and P < 0.001 ), and lymphocyte counts (OR = 0.522, 95% CI = 0.333–0.819, and P = 0.005 ) were significantly associated with HT. Conclusions . High NLR could be a useful marker for predicting HT in AIS patients after IVT.